Optimizing Lakesla Health Support for Indonesian Navy Divers Through Hyperbaric Services: An Analysis of Challenges and Strategies to Support the Main Tasks of the Indonesian Navy - Ilfan, Muhamad; Bay, Aminul Ummah; Wijiantoro, Hendro (Journal of Industrial Engineering & Management Research, 2025)
Navy divers of the Indonesian Navy face serious health risks due to activities in extreme pressure environments, such as decompression and gas embolism. As a naval military health institution, Lakesla holds a strategic role in providing hyperbaric therapy to ensure divers’ readiness and safety. This study analyzes three main aspects: challenges in the implementation of hyperbaric services, their contribution to operational readiness and diver safety, and optimization strategies to sustainably support the main tasks of the Indonesian Navy. The research employs a qualitative approach through in-depth interviews, field observations, and documentation, with data analysis conducted using NVivo software, triangulation, and a SWOT framework enhanced by the IFAS–EFAS matrix. The findings indicate that Lakesla has strengths in representative hyperbaric facilities, competent medical personnel, and institutional support from the Navy, yet faces constraints in certified human resources, limited equipment maintenance budgets, and suboptimal information systems. External opportunities, including increased diving operations, technological advancements, and potential inter-institutional cooperation, outweigh existing threats, positioning Lakesla in Quadrant I (aggressive strategy). Hyperbaric services have been proven to significantly contribute to the readiness and safety of Navy divers. Optimization can be achieved through integrating services within Navy operational systems, strengthening human resource competence, digitalizing diver medical records, and enhancing research and educational outreach. With these strategies, Lakesla has the potential to evolve into a modern, adaptive, and sustainable center of excellence in diving medicine.